The Value at Risk of Selling Option on Crude Oil West Texas Intermediate - Abitur Asianto; Hermanto Siregar; Roy Sembel; Tubagus Nur Ahmad Maulana (ETIKONOMI, 2019)
The Value at Risk (VaR) of selling the option on crude oil WTI has not widely known, whereas this trade is the most significant transactions in the world. This study aimed to analyze the Value at Risk (VaR) of the far out of the money (FOTM) and the in the money (ITM) strike position of selling option on crude oil WTI investment. The monthly option premium return data ranging from April 1984 to May 2017 was analyzed by the ARCH-GARCH and VaR method to get the risk of FOTM and ITM strike position. Empirical results indicate that the risk of the FOTM strike was much lower than the ITM strike positions. It meant that selecting the FOTM strike position of the selling option on crude oil WTI investment could be considered by stakeholders because its risk was much lower than the ITM strike position.JEL Classification: C32, G19, G32